Phonological Shift among Generation Z: The Impact of Social Media on Acehnese Accents in Coastal Areas - Cut Faizah; Sabrina Sabrina; Nyak Mutia Ismail (International Journal of Education, Language, and Religion, 2025)
This study investigates phonological shift and accent erosion among Generation Z Acehnese speakers in the West–South coastal region, focusing on the role of social media. Adopting a descriptive-qualitative design, we gathered speech recordings from targeted stimulus sentences, in-depth interviews, and field observations with youth in Meulaboh and Calang, and contrasted them with an adult control group. Praat-assisted analysis traced changes in vowel and consonant realization, stress, and intonation. Findings show systematic simplification: diphthongs such as /eu/ and /oe/ frequently monophthongize to /e/ or /o/; nasal and guttural consonants weaken (e.g., /ng/→/n/, /kh/→/k/); final consonants are dropped in fast speech; and prosody flattens, with Indonesian-like contours replacing Acehnese rise–fall patterns in both declaratives and questions. Interview evidence links these shifts to intensive exposure to standard-language models on TikTok, YouTube, and Instagram; code-switching in online interaction; migration to urban centers; and household language policies that prioritize Indonesian for mutual comprehension. The study offers phonology-level evidence of accent erosion in Aceh and clarifies how digital culture mediates language change among minority-language youth. Implications include producing Acehnese-language digital content, integrating phonological awareness into local curricula, and designing community programs that valorize prosody and segmental features. While limited to two towns and a modest sample, the findings provide a baseline for longitudinal monitoring and comparative work across districts and age cohorts, and inform preservation strategies that balance modernization with the maintenance of Acehnese phonological distinctiveness.